The perception of the Lampanah community towards community service lectures of Al Washliyah Banda Aceh disciple students - Z, Rizwan; Bariah, Chairul; Fitria Hamda, Erna; Jasmadi, Jasmadi; Lasri, Lasri; Ilham, Ilham (Institute of Education and Social Research, 2024)
The Community Service Program (KPM) is a university initiative aimed at applying students' knowledge and skills to contribute directly to the community. In Lampanah Settlement, Seulimeum District, Aceh Besar Regency, the KPM program implemented by STISIP Al Washliyah Banda Aceh students is expected to have a positive impact on the community. However, community perceptions of this program need to be evaluated to ensure the effective implementation of KPM activities. This study aims to analyze the perceptions of the Lampanah Settlement community towards the KPM program by STISIP Al Washliyah Banda Aceh students. The research employs a mixed-methods approach, with data collection techniques including interviews, observation, and documentation. The sampling technique used the Slovin formula, distributing e-questionnaires to 212 samples from a total population of 450, with a 5% margin of error in Lampanah Settlement. The results show that: 1) 65% of respondents had a positive perception, 20% were neutral, and 25% were negative; 2) 70% of respondents viewed the benefits of the activities as high, 15% as moderate, 6% as neutral, and 4% as low; 3) Communication barriers included language (20%), cultural differences (45%), and technological constraints (25%). Interviews revealed that the Lampanah Settlement community generally had a positive perception of the KPM program, appreciating students' contributions to education, health, and economic empowerment. However, factors such as ineffective student communication and limited community involvement in planning and implementing programs were identified as areas needing improvement.